Forests, protest movements and the struggle over meaning and identity in Sarawak - Fadzilah Majid Cooke (Universiti Kebangsaan Malaysia, 1999)
Widespread rural protest against forestry actitities in Sarawak during the mid 1980s and early 1990s invited retaliatory measures from the state in the form of tighter surveillance and criminalisation of protest. Thus, the protest movement could easily be dismissed as having failed to influence policy. However, in the long history of Dayak protest against forestry activities what may be new is the widespread and sustainded nature of the action. But how was strategic mobilisation possible, given the limited political space for critique, the lack of political cohesion and the heterogeneity of Dayak experience of the state and ‘development’? Viewing Dayak protests as part of an ongoing larger social movement concerned with a more just state and environmental health, the paper highlights the way in which rural protest assists in the production of ‘Dayakised’ knowledge about development, environment and identity. In this larger movement, the work of academic researchers, environmental and indigenous activists are linekd. The paper argues that the implications of the protests for rural Dayak understadning and experience of the state, citizenship and identity is far reaching but, as yet, little understood, suggesting a need for analysis of the state and civil society to move beyond party politics and the NGO movement. What the movement has done is expand the discourse and practice of conservation to include a wider range of concerns than have been possible in the past, given the tendency to privilege biological and economistic factors in resource management policy.